Incidence of Dry Eye Syndrome After Cataract Surgery with Phacoemulsification Technique in Padang Eye Center Hospital: Poster Presentation - Observational Study - General practitioner - Khalieta, Amanda; Sastra, Joni (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Dry eyes is one of the most common ophthalmological problems. The etiology of dry eyes is usually multifactorial, such as medication, aging, systemic disease, allergy, computer usage, environmental factors, meibomian gland dysfunction and ophthalmic surgery. Cataract is still one of the leading causes of vision impairment globally. No medical treatment is effective to remove cataract. Thus, the only option is cataract removal surgery. The most common technique of cataract surgery in Padang Eye Center Hospital is phacoemulsification. This study aims to assess the incidence of dry eye syndrome after phacoemulsification surgery without complication in patients with no previous history of dry eye syndrome. Methods : This study was conducted using a prospective study. The evaluation uses Ocular Surface Disease Index ( OSDI ) questionnaire and tear break-up time ( TBUT ) test performed preoperatively and three times postoperatively at one week, one month and three months follow-up after surgery. Results : 110 eyes of 96 patients diagnosed with cataracts who had undergone phacoemulsification surgery were enrolled in this study. The mean age of patients is 62.46 ± 6.14 years, and 59,09% were men. After one week of surgery, only 9,09% had results 0-12 on the OSDI scale, and 43,63% represented moderate dry eye disease ( OSDI score 23-32 ) and TBUT test results from 61,82% of patients had dry eyes, which improved gradually after time. Conclusion : The incidence of dry eye syndrome significantly increased after one-week post-surgery. But after one month postoperative, the patients’ condition gradually improved and returned to normal after three months postoperatively.